2004
DOI: 10.1097/00006199-200411000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Nursing Work Environment of Critical Care Nurses

Abstract: The PNWE, a measure of the work environment as perceived by nurses, represents the latest version of the Nursing Work Index-Revised based on current practice. In this study, it exhibited sound psychometric properties. Further application and testing of the PNWE in various patient care settings is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
135
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(152 citation statements)
references
References 16 publications
13
135
2
2
Order By: Relevance
“…In contrast, greater availability of support services was associated with higher levels of work engagement and better work conditions. These findings have been similarly documented in other studies (Cimiotti et al, 2005;Choi, Bakken, Larson, Du, & Stone, 2004;Mark et al, 2003;McCusker, Dendukuri, Cardinal, Laplante, & Bambonye, 2004). Patient acuity and unit size, however, did not have a direct effect on structure because we limited the sample to medical-surgical units, and in so doing, restricted variability in patient acuity and unit size in our sample.…”
Section: Effect Of Organizational Context On Structuresupporting
confidence: 85%
“…In contrast, greater availability of support services was associated with higher levels of work engagement and better work conditions. These findings have been similarly documented in other studies (Cimiotti et al, 2005;Choi, Bakken, Larson, Du, & Stone, 2004;Mark et al, 2003;McCusker, Dendukuri, Cardinal, Laplante, & Bambonye, 2004). Patient acuity and unit size, however, did not have a direct effect on structure because we limited the sample to medical-surgical units, and in so doing, restricted variability in patient acuity and unit size in our sample.…”
Section: Effect Of Organizational Context On Structuresupporting
confidence: 85%
“…The sample profile did not differ from other surveys conducted. (4,(8)(9)(10) With regard to gender, the prevalence was feminine, and when it came to age, the majority were young nurses. A discrepancy was only found in one study that observed an average age of 39.6 years and professional activity time in intensive care units of eight years.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these authors did generally find significant associations between safety climate and adverse hospital outcomes. They concluded 39) . This scale was derived from the NWI-R 31) and has similar items.…”
Section: Safety Climatementioning
confidence: 99%
“…Organizational climate was measured using the PNWE 39) ; here organizational climate as well as nurse demographics was controlled for in examining the independent effect of shift length on burnout. They found that nurses working 12-h shifts were significantly less likely than nurses working 8-h shifts to report one of the dimensions of burnout, namely emotional exhaustion.…”
Section: Burnoutmentioning
confidence: 99%